The Effect of Health Education on Preventing Pulmonary Tuberculosis Transmission with Knowledge Deficit Problems Through Audiovisual Media - Susyanti, Eny; Ayu Adiningsih, Yuni (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: The aim of this research is to determine the effect of health education on preventing transmission of pulmonary tuberculosis with knowledge deficit problems through audiovisual media before and after health education is carried out. Method: the research method used is descriptive with a case study approach. The research subjects were 43 respondents taken using the minimum sample in the Slovin formula. Result: the results showed that there was an increase in the level of knowledge from before health education was carried out, namely in the category of insufficient level of knowledge of 32 respondents (74%) to 0 respondents (0%), in the category of sufficient level of knowledge of 11 respondents (26%) to 2 respondents (5 %), The good knowledge level category was 0 respondents (0%) to 41 respondents (95%). Conclusion: Thus, it can be concluded that health education to prevent transmission of pulmonary tuberculosis with the problem of knowledge deficit through audiovisual media can have an influence in increasing knowledge among respondents